Creating Environmental Awareness using an Eco-Feedback Application at a Higher Education Institution - Andre Calitz; Margaret Cullen; Francois Odendaal (Environmental Association of Southern Africa, 2020)
Providing environmental education and creating environmental awareness assists future generations to conserve, preserve and sustain the environment. Organisations are supporting environmental awareness education efforts and universities are increasingly being required to exercise sound environmental behaviour and educate all stakeholders on their responsibility of being aware of their environmental impact. Gamification and eco-feedback applications in previous studies have been used to provide feedback on an individual's behaviour with the goal of creating environmental awareness. Students are generally not provided with environmental information regarding their use of electricity, water and waste management whilst on campus. In this exploratory study, an eco-feedback application was developed and used to create environmental awareness amongst postgraduate students at the Nelson Mandela University and the functionality of the eco-feedback application was evaluated. The results indicated that participants became more aware of their environmental impact after being exposed to an eco-feedback application. The functionality provided by the eco-feedback application, to assist in creating environmental awareness within an academic institution, proved to be useful.